Analisis Kestabilan Model Insidensi Setengah Jenuh pada Epidemi Flu Burung - Yomi Kharisma Septika; Ali Kusnanto; Paian Sianturi (Jurnal Matematika, 2021)
Abstract: The H5N1 avian influenza is an example of a pathogen that is known to cause human disease outbreaks. This study focuses on selecting avian influenza control strategies using Half-Saturated Incidence (HSI) Models. In this study, a model was constructed by involving elements of human self-protection, poultry isolation and poultry vaccination. Furthermore, it is shown that the parameters that influence are the parameters of the population that apply personal protection and its effectiveness, the parameters of the rate of isolation of birds with avian influenza, and the parameters of vaccine coverage and its effectiveness. Increasing the value of this parameter can reduce the basic reproduction number so that disease-free conditions can occur. Hence, controlling the dynamics of disease spread can be done by increasing the value of these parameters.